A Comparative Analysis of the Efficacy of the General Anti-Avoidance Rule as a Measure Against Impermissible Income Tax Avoidance in South Africa - Fanzsen, Riel (University of Pretoria, 2014)
Thesis (LLD)--University of Pretoria, 2013.